(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This in the article Rhesus immunization encountered pregnant in women and their new born in babies cytokine status analysis Research during the II and III trimesters Rhesus immunization 40 identified pregnant woman , also intrauterine blood casting practice done and traditional treated new born in babies cytokines profile studied. Research results IL-6 and TNF- α level increase inflammation processes increase in IL-10 levels decrease and to inflammation against the answer to weaken showed. Intrauterine blood casting technology hemolytic of processes weight in reduction efficiency with separated stood. This neonatal hemolytic results the disease prevent to take and treatment for important clinical the basics presented will reach.